Wastewater treatment plants, an “escape gate” for ESCAPE pathogens - Marutescu, Luminita Gabriela; Popa, Marcela; Gheorghe-Barbu, Irina; Barbu, Ilda Czobor; Rodríguez-Molina, Daloha; Berglund, Fanny; Blaak, Hetty; Flach, Carl-Fredrik; Kemper, Merel Aurora; Spießberger, Beate; Wengenroth, Laura; Larsson, D. G. Joakim; et al. (Frontiers in Microbiology, 2023)
Antibiotics are an essential tool of modern medicine, contributing to significantly decreasing mortality and morbidity rates from infectious diseases. However, persistent misuse of these drugs has accelerated the evolution of antibiotic resistance, negatively impacting clinical practice. The environment contributes to both the evolution and transmission of resistance. From all anthropically polluted aquatic environments, wastewater treatment plants (WWTPs) are probably the main reservoirs of resistant pathogens. They should be regarded as critical control points for preventing or reducing the release of antibiotics, antibiotic-resistant bacteria (ARB), and antibiotic-resistance genes (ARGs) into the natural environment. This review focuses on the fate of the pathogens Enterococcus faecium, Staphylococcus aureus, Clostridium difficile, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacteriaceae spp. (ESCAPE) in WWTPs. All ESCAPE pathogen species were detected in wastewater, including high-risk clones and resistance determinants to last-resort antibiotics such as carbapenems, colistin, and multi-drug resistance platforms. The whole genome sequencing studies demonstrate the clonal relationships and dissemination of Gram-negative ESCAPE species into the wastewater via hospital effluents and the enrichment of virulence and resistance determinants of S. aureus and enterococci in WWTPs. Therefore, the efficiency of different wastewater treatment processes regarding the removal of clinically relevant ARB species and ARGs, as well as the influence of water quality factors on their performance, should be explored and monitored, along with the development of more effective treatments and appropriate indicators (ESCAPE bacteria and/or ARGs). This knowledge will allow the development of quality standards for point sources and effluents to consolidate the WWTP barrier role against the environmental and public health AR threats.